2014
DOI: 10.3390/ijerph110201261
|View full text |Cite
|
Sign up to set email alerts
|

Embedded Fragments from U.S. Military Personnel—Chemical Analysis and Potential Health Implications

Abstract: Background: The majority of modern war wounds are characterized by high-energy blast injuries containing a wide range of retained foreign materials of a metallic or composite nature. Health effects of retained fragments range from local or systemic toxicities to foreign body reactions or malignancies, and dependent on the chemical composition and corrosiveness of the fragments in vivo. Information obtained by chemical analysis of excised fragments can be used to guide clinical decisions regarding the need for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 26 publications
0
24
0
Order By: Relevance
“…Such concern has driven the Department of Veterans Affairs to conduct bio-monitoring on patients who have suffered injuries from improvised explosive devices (IED) during the recent Iraq and Afghanistan conflicts. Through fragment content analysis, a suite of 14 metals has been identified to comprise the most commonly observed metal components of surgically removed fragments from IED injured service members [Centeno et al, 2014]. Because the DU penetrator was not solely composed of DU, but was alloyed with titanium , and due to raised concern regarding the release and potential toxicity of metal ions from DU and non-DU retained fragments as described above, the bio-monitoring battery has been enlarged to include this suite of metals encountered in IED, as well.…”
Section: Surveillance For Other Metals In Fragment Alloysmentioning
confidence: 99%
See 1 more Smart Citation
“…Such concern has driven the Department of Veterans Affairs to conduct bio-monitoring on patients who have suffered injuries from improvised explosive devices (IED) during the recent Iraq and Afghanistan conflicts. Through fragment content analysis, a suite of 14 metals has been identified to comprise the most commonly observed metal components of surgically removed fragments from IED injured service members [Centeno et al, 2014]. Because the DU penetrator was not solely composed of DU, but was alloyed with titanium , and due to raised concern regarding the release and potential toxicity of metal ions from DU and non-DU retained fragments as described above, the bio-monitoring battery has been enlarged to include this suite of metals encountered in IED, as well.…”
Section: Surveillance For Other Metals In Fragment Alloysmentioning
confidence: 99%
“…These metals were chosen based on their presence in analyzed embedded fragments [Centeno et al, 2014] and their potential toxicity and carcinogenicity [Gaitens et al, 2010]. Preparation of urine samples and metal analysis by sector field high resolution ICP-MS were conducted as described by Gray .…”
Section: Exposure Assessment For Uranium and Other Metals Of Concernmentioning
confidence: 99%
“…Reported by Centeno et al 10 as commonly found in embedded fragments removed from military personnel.…”
Section: Presentation Resultsmentioning
confidence: 98%
“…The infrequency of these events further complicates efforts to identify and remove fragments and to identify and monitor patients at risk 68,69 . While most fragments from combat‐related injuries contain a mixture of metals, iron, copper, and aluminum have been found to be the main components 10 . The presence of lead, tungsten, and DU in embedded fragments is less common 10 .…”
Section: Presentation Resultsmentioning
confidence: 99%
See 1 more Smart Citation